Analysis of performance practice through comparison of multiple recordings : The Sonata No.1 in C (op.1) by Johannes Brahms (1833-1897) / Lee Seow Phing - Lee, Seow Phing (2015)
This dissertation analyzes temporal deviations across for performance by different pianists’ of the Sonata No.1 in C by Johannes Brahms, in order to posit inferences of emotional expression. The timing deviations were analysed using Audacity, then collated in Microsoft Excel 2010. The results were placed within two-dimensional graphs to show timing variations relative to the sections of Sonata form: Exposition, Development, Recapitulation and Coda. The timings were arranged according to the standard deviation (SDs) from the group mean of (495.705 ± 55.794) seconds, ranging from 418.230 seconds to 615.799 seconds. Interestingly, the lowest timing (fastest performance) was well over a minute faster than the mean and the highest timing (slowest performance) was over one and a half minutes from the mean. Grouping performances by similarities or differences within the 1SD , 2 SDs and beyond were useful guides to performing time in pianists. Inferences regarding a relation between timing and emotion were achieved through derivation in the standard deviation index (SDI) which is an analogue of emotional index (EI) through the variable of Time. Systematic treatment to emotion contours identified in excerpts from the 2nd themes in various sections were quantified in ( EI) for contours should they contain significant structure signalling emotional features of music graded as levels of expression ( EI) in undulating tension relaxation relationships.